The power of sunspots: An experimental analysis - Dietmar Fehr; Frank Heinemann; Aniol Llorente-Saguer (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
We present an experiment in which extrinsic information (signals) may generate sunspot equilibria. The underlying coordination game has a unique symmetric non-sunspot equilibrium, which is also risk-dominant. Other equilibria can be ordered according to risk dominance. We compare treatments with different salient, but extrinsic signals. By increasing the precision of private signals, we manipulate the available public information, which allows us to measure the force of extrinsic signals. We also vary the number of signals and combine public and private signals, allowing us to see how subjects aggregate available (and possibly irrelevant) information. Results indicate that sunspot equilibria emerge naturally if there are salient (but extrinsic) public signals. However, salient private signals of high precision may also cause sunspot-driven behavior, even though this is no equilibrium. The higher the precision of signals and the easier they can be aggregated, the more powerful they are in dragging behavior away from the risk-dominant to risk-dominated strategies. Sunspot-driven behavior may lead to welfare losses and exert negative externalities on agents, who do not receive extrinsic signals.
Keywords: C72; C92; D84; 330; coordination games; strategic uncertainty; sunspot equilibria; irrelevant information; Nichtkooperatives Spiel; Koordination; Sunspot; Gleichgewicht; Test